Oxytocin and Social Bonds: The Role of Oxytocin in Perceptions of Romantic Partners' Bonding Behavior. (December 2017) - Algoe, Sara B.; Kurtz, Laura E.; Grewen, Karen
In this research, we tested hypotheses about the role of oxytocin in adult human bonding. Inspired by revisiting the research on pair bonding in microtine voles that fueled psychologists' interest in the role of oxytocin in social life, we drew on recent theory from affective and relationship science to identify a well-defined bonding context for human romantic relationships. We then paired these behaviors and subjective psychological responses with a measure of naturally circulating oxytocin. In 129 romantically involved adults whose partner expressed gratitude to them in the lab, greater oxytocin over the prior 24 hr was associated with greater perceptions of the expresser's responsiveness and gratitude, as well as greater experienced love, but not general affective reward. Moreover, in this one-time conversation, higher oxytocin acted like rose-colored glasses, attenuating the effect of a partner's behaviorally coded expressive behavior on perceptions of the expresser's responsiveness. These results justify future research on the role of oxytocin in psychological aspects of growth processes.